Ligustrazine Injection in the Treatment of Acute Ischemic Stroke: a Bayesian Network Meta-analysis - NIU Jingyuan, CHEN Huisheng, YU Jiaxiang, CUI Yu (Zhongguo quanke yixue, 2024)
Background Acute ischemic stroke (AIS) is a serious cerebrovascular disease, which causes a heavy burden on society and patients. Ligustrazine injection has been widely used in the treatment of AIS with significant efficacy, but there is still a lack of direct or indirect comparison between ligustrazine injections. Objective To systematically evaluate the efficacy and safety of ligustrazine injection in the adjuvant treatment of AIS within 72 hours. Methods CNKI, Wanfang Data Knowledge Service Platform, VIP, PubMed, Cochrane Library, Embase, and Web of Science databases were searched for randomized controlled trials (RCTs) about the efficacy and safety of ligustrazine injection in the treatment of AIS from inception to April 2023. Literature was independently screened, extracted and quality assessed by 2 investigators using the Cochrane Evaluation Tool. RevMan 5.3, Stata 17, Addis and RStudio software were used to statistically compare and rank the efficacy and safety of different types of ligustrazine injection. Results A total of 71 papers involving 7 304 cases were included, and the interventions included Salvia Miltiorrhiza Ligustrazine Injection (DSCXQ), Shenxiong Glucose Injection (SXPTT), Xingxiong Sodium Chloride Injection (XXLHN), Ligustrazine Phosphate Injection (LSCXQ) and Ligustrazine Hydrochloride Injection (YSCXQ) combined with conventional western medical therapy (CT), respectively, and CT alone. Direct Meta-analysis results showed that in improving all the outcome indicators of AIS, the total effective rate, NIHSS score, fibrinogen level, and incidence of adverse reactions of ligustrazine injection combined with CT were better than those of CT alone (P<0.05). The results of network Meta-analysis showed that the order of cumulative probability in total effective rate was SXPTT+CT (0.60) >YSCXQ+CT (0.20) >LSCXQ+CT (0.15) >DSCXQ+CT (0.03) >XXLHN+CT (0.02) >CT (0) ; the order of cumulative probability in improving NIHSS score was SXPTT+CT (0.55) >XXLHN+CT (0.26) >YSCXQ+CT (0.12) >DSCXQ+CT (0.07) >CT (0) ; the order of cumulative probability in reducing fibrinogen level was XXLHN+CT (0.32) >LSCXQ+CT (0.22) >DSCXQ+CT (0.17) >SXPTT+CT (0.15) >YSCXQ+CT (0.14) >CT (0) ; the order of cumulative probability in safety was SXPTT+CT (0.79) >XXLHN+CT (0.13) >CT (0.04) >DSCXQ+CT (0.03) >YSCXQ+CT (0.01) . Conclusion Ligustrazine injection is effective and safe in adjuvant treatment of AIS, among which Shenxiong glucose injection was the best in total effective rate and improving NIHSS scores, with the least adverse reactions; Xingxiong sodium chloride injection has the most advantages in fibrinogen level.